Macrophage efferocytosis in health and disease - Razi, Shokufeh; Yaghmoorian Khojini, Javad; Kargarijam, Fateme; Panahi, Susan; Tahershamsi, Zahra; Tajbakhsh, Amir; Gheibihayat, Seyed Mohammad (Cell biochemistry and function, 2023)
Creating cellular homeostasis within a defined tissue typically relates to the processes of apoptosis and efferocytosis. A great example here is cell debris that must be removed to prevent unwanted inflammatory responses and then reduce autoimmunity. In view of that, defective efferocytosis is often assumed to be responsible for the improper clearance of apoptotic cells (ACs). This predicament triggers off inflammation and even results in disease development. Any disruption of phagocytic receptors, molecules as bridging groups, or signaling routes can also inhibit macrophage efferocytosis and lead to the impaired clearance of the apoptotic body. In this line, macrophages as professional phagocytic cells take the lead in the efferocytosis process. As well, insufficiency in macrophage efferocytosis facilitates the spread of a wide variety of diseases, including neurodegenerative diseases, kidney problems, types of cancer, asthma, and the like. Establishing the functions of macrophages in this respect can be thus useful in the treatment of many diseases. Against this background, this review aimed to recapitulate the knowledge about the mechanisms related to macrophage polarization under physiological or pathological conditions, and shed light on its interaction with efferocytosis. Significance statement Efferocytosis occurs to remove apoptotic cells by phagocytic ones, in particular macrophages. Any insufficiency in macrophage efferocytosis facilitates the spread of a wide variety of diseases, including autoimmune disorders, neurodegenerative diseases, kidney problems, types of cancer, asthma, and the like. Recent research has established that macrophage polarization can affect the efferocytosis process. A better understanding of macrophage polarization and its cytokines in many diseases can help design treatments to improve patient outcomes.